Integration of Therapeutic Components in the Rehabilitation of Patients with Parkinson's Disease - Sonia Viviané Jiménez Carpi; Jorge Luis Abreus Mora; Vivian Bárbara González Curbelo; Ernesto Julio Bernal Valladares; Fernando Jesús Del Sol Santiago (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Currently, there is a trend towards the inclusion of rehabilitation therapies as a complement to the pharmacological treatment of patients with Parkinson's disease, which leads to a transition to interdisciplinary management. This systematic review analyzed as problem, the integration of physical therapies and therapeutic components during physical rehabilitation process. Its objective was to assess the patient´s integration, therapist and family components during the physical rehabilitation process of people with Parkinson's. Selection criteria were established to homogenize the selected sample. The studies were chosen through a search, from January 2017 to October 2018. The following databases were searched: Science Direct, SciELO, EMBASE (Excerpta Médica), Medline, Elsevier, Scopus, Pudmed. The established descriptors were: [Parkinson's disease or physical activity and Parkinson's disease], [physical interventions in Parkinson's disease or physical therapies in Parkinson's disease] and [rehabilitation in Parkinson's disease or family and Parkinson's disease]. As a result, 13 articles were selected which met the criteria, using the PEDro scale the methodological quality was evaluated and the importance of physical capacities restoration during motor rehabilitation of these people was highlighted. For its approach, it was also proposed to integrate rehabilitation process components. Therapeutic components must be integrated into studies of this condition: patient, as the main center of attention; therapist, who is most responsible for leading the rehabilitation process and family, for the role it plays within the process.